Recommendations of individualized medical treatment and common adverse events management for lung cancer patients during the outbreak of COVID‐19 epidemic - Zhao, Zhe (Thorac Cancer, 2020)
Since its outbreak in December 2019 in China, the novel coronavirus disease (COVID‐19) has rapidly spread and affected several countries. It has resulted in a difficult situation for cancer patients owing to the risks of the epidemic situation outbreak as well as cancer. Patients with cancer are more likely than the general population to contract COVID‐19 because of the systemic immunosuppressive status caused by malignant diseases or anticancer treatment. Lung cancer has the highest morbidity and mortality in China and the world. Most patients with lung cancer are smokers with poor underlying lung conditions and low immunity, thus it is vital to protect them from epidemic diseases during cancer treatment. It is necessary to provide individualized medical treatment and management of treatment‐related adverse events for patients with lung cancer based on patients' conditions and regional epidemic patterns. KEY POINTS: Significant findings of the study During the outbreak of COVID‐19, taking patients' conditions and regional epidemic patterns into consideration, providing appropriate individualized treatment strategies for lung cancer patients with different stages is an urgent requirement. What this study adds Based on the characteristics of lung cancer, this article aims to provide recommendations and suggestions of individualized treatment strategies and management of common adverse events for patients with lung cancer during the epidemic period of COVID‐19.